Patterns and prevalence of depression, tobacco, and caffeine use among university students from different majors in Lebanon: a cross-sectional study - El Hashem, Afife; Bou Saba, Angela; Bou Madi, Anna Maria; Mahfouz, Caroline; Derian, Clara; El Husseiny, Elie; Hanna, Jeanne-Marie; El Hayek, Maguy; Assaad, Shafika (Frontiers in Public Health, 2025)
BackgroundMental health plays a fundamental role in overall wellbeing, with depression being one of the most common mental health disorders worldwide. University students face significant academic, financial, and social pressures, making them particularly vulnerable to depression. Research showed difference in consumption of psychoactive substances such as caffeine and tobacco among genders and academic fields. It suggests also a link between the use of these substances and an increase in depressive symptoms. The consumption of these substances among all university students in Lebanon from multiple majors and the relationship between this intake and mental health remains underexplored.Materials and methodsThis cross-sectional study surveyed university students across Lebanon to assess their tobacco and caffeine consumption and its relationship with depression. A self-administered online questionnaire, including the Beck Depression Inventory, was used to measure depression levels and collect data on substance use patterns. A total of 626 convenient responses were analyzed, incorporating both descriptive and inferential statistical analyses.ResultsThe study found that 31.15% of university students experienced some level of depression. Gender differences were observed in tobacco and caffeine consumption: cigarette smoking was significantly higher among males (25%) than females (7.4%), while no significant gender-based differences were found for electronic cigarette and shisha use. Among caffeinated products, chocolate was the most consumed (92.9% males, 98.1% females), followed by other types of coffee (71.9% males, 80.5% females). Significant gender differences were noted in Arabic coffee, chocolate, tea, and cigarette consumption, but not for energy drinks, e-cigarettes, or waterpipes. Depression levels did not significantly differ between genders for most substances, except for cigarette smoking, where female smokers exhibited significantly higher depression scores than male smokers (p = 0.032). Additionally, depression levels varied across academic majors, with architecture students displaying the highest levels and medical students the lowest. Tobacco consumption is higher among non-medical majors, whereas caffeine is higher among health and non-medical majors.ConclusionThis study highlights the need for targeted mental health interventions, awareness campaigns, and accessible psychological support services for university students. Future research should explore additional sociocultural factors influencing substance use and mental health.